1999
DOI: 10.1002/(sici)1521-3757(19990712)111:13/14<2199::aid-ange2199>3.0.co;2-y
|View full text |Cite
|
Sign up to set email alerts
|

Ein Molybdän-Eisen-Schwefel-Cluster mit Strukturelementen des Nitrogenase-P-Clusters

Abstract: Eisen‐Molybdän‐Cofaktor und P‐Cluster sind zwei essentielle Komponenten in Fe‐Mo‐Nitrogenasen. Erstmals gelang die Synthese eines Clusters, dessen Fragmente wesentliche Strukturmerkmale des Nitrogenase‐P‐Clusters aufweisen. Die im Bild gezeigte Verbindung, ein Cluster der Zusammensetzung Mo6Fe20S30, wurde durch Einkristall‐Röntgenstrukturanalyse und 57Fe‐Mößbauer‐Spektroskopie charakterisiert.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2004
2004
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(1 citation statement)
references
References 21 publications
0
1
0
Order By: Relevance
“…There have been numerous examples of high nuclearity transition metal clusters encapsulating S (Allen, 2002). Such SM 6 clusters have been reported for Fe (Zhang et al, 2002(Zhang et al, , 2003(Zhang et al, , 2004Zuo et al, 2003;Osterloh et al, 1999;Ohki et al, 2003), Cu (Wu, et al, 1988;Marsh, 1997;Hu, 2001;Lin et al, 2000a;Chen et al, 2003;Tang et al, 1993), Co (Shu et al, 1991), Zr (Fenske et al, 1991) and Ag (Chen et al, 2004;Lin et al, 1997;Matsumoto et al, 2000;Lin et al, 2000b;Jin et al, 1996), while SM 8 clusters have been reported for Rh (Vidal et al, 1978) and Cu (Lin et al, 1999;Huang et al, 1991;Dehnen & Fenske, 1996, Liu et al, 1995Fenske et al, 2004). With the exception of one report of an SLi 8 cluster (Banister et al, 1988), there has been no report of an SM x cluster involving a non-transition metal.…”
Section: Commentmentioning
confidence: 95%
“…There have been numerous examples of high nuclearity transition metal clusters encapsulating S (Allen, 2002). Such SM 6 clusters have been reported for Fe (Zhang et al, 2002(Zhang et al, , 2003(Zhang et al, , 2004Zuo et al, 2003;Osterloh et al, 1999;Ohki et al, 2003), Cu (Wu, et al, 1988;Marsh, 1997;Hu, 2001;Lin et al, 2000a;Chen et al, 2003;Tang et al, 1993), Co (Shu et al, 1991), Zr (Fenske et al, 1991) and Ag (Chen et al, 2004;Lin et al, 1997;Matsumoto et al, 2000;Lin et al, 2000b;Jin et al, 1996), while SM 8 clusters have been reported for Rh (Vidal et al, 1978) and Cu (Lin et al, 1999;Huang et al, 1991;Dehnen & Fenske, 1996, Liu et al, 1995Fenske et al, 2004). With the exception of one report of an SLi 8 cluster (Banister et al, 1988), there has been no report of an SM x cluster involving a non-transition metal.…”
Section: Commentmentioning
confidence: 95%